Preliminary finding of psychometric properties of the existing quality assurance evaluation model (QAEM) for National Universities Commission (NUC) of the federal republic of Nigeria - Bolaji, Bojuwon Yusuf; Mohd Ali, Hairuddin (2013)
The measure of quality assurance evaluation plays a vital role in quality enhancement determinations, precisely in university educational institutions. Recently, Nigeria Government had to embark on laudable policy programmes that will enhance the quality of university educational institutions. But to fulfill this responsibility, is frequently thwarted by long- standing challenges of access, inadequate funding, facilities, governance, curriculum problem, human resource and technology input. The challenges face by university educational institutions have led to a rigorous quest for this research. The drive of this research was accompanied to test and evaluate its psychometric properties of the existing QAEM Input process (IP) NUC accreditation instruments and as well to examine the dimensionality, reliability and construct's validity using a confirmatory factor's analysis approach) of QAEM instruments in order to enhance the quality of evaluation of the nation’s university education system. To this end, the research employs a cross-sectional survey data approach collected from the survey of 16 universities. Data has been collected using the personal contact approach suggested by Sureshchandar et al., (2004). A total of 1600 survey/questionnaires were distributed and data has been collected from sixteen universities, which represent one thousand six hundred (1600) respondents. This is in line with the guideline for sample size decisions as proposed by Krejcie and Morgan, (1970). The respondents cutting across all spheres of the university community which includes vice-chancellors (university administrators), management teams, NUC staff, Teaching staff and non- teaching staff, director/deans/HODs and students in the North Central Geo- Political Zone of Nigeria. Nevertheless, these preliminary reports employed quota sampling technique for selecting survey participants. Factor extracted was achieved using an Exploratory Factor Analysis (EFA), Principal Component Analysis (PCA)(using SPSS 18.0) and measurement model of confirmatory factor analysis (CFA) techniques was performed to extract the fundamental factors, to check for factorial validity of the dimensional constructs and to screen the instruments into appropriate QAEM dimensions(though Structural Equation modeling (SEM) using AMOS 18.0.